User-generated Translation: The future of translation in a Web 2.0 environment - Silvio Perrino (JoSTrans: The Journal of Specialised Translation)
The purpose of this paper is to investigate how translation activities can be carried out using available online tools. In Section 1 of this paper, I intend to illustrate how mass collaboration happens in the so-called Web 2.0 – a term coined by Tim O'Reilly in 2005 to describe a number of services which enable today's Internet users to interact and share information efficiently. The innovations of Web 2.0, along with the controversial issues to which they give rise, will be presented, before being applied to translation in Section 2. Subsequently, I will introduce the concept of User-generated Translation (UGT), an umbrella term I use to define translation practices made possible by various online services. I call such services UGT tools and classify them according to the nature of the content for which they offer means of translation. In Section 3, seven tools will be introduced and reviewed according to established parameters, such as ease of use and user participation. The data thus gathered will be compiled in tables for at-a-glance review. In the final chapter, I conclude that User-generated Translation is feasible but that, at present, the available tools and their users cannot compete with the professional translation industry.